Analisis Keluhan Muskuloskeletal pada Pengemudi Mobil Prototype Menggunakan Metode Nordic Body Map - Farid Khairul; Wanda Afnison; Irzal Irzal; Milana Milana (Unversitas Negeri Padang, 2025)
The depletion of fossil energy reserves, especially oil and natural gas, has driven innovations in energy-efficient vehicles, including through the Energy-Efficient Car Contest (KMHE). In developing prototype cars for this competition, driver ergonomics is often overlooked. This study aims to analyze musculoskeletal complaints experienced by prototype car drivers from the Faculty of Engineering at UNP. The main instrument used was the Nordic Body Map (NBM) questionnaire, administered to three drivers after they performed a 20-minute static driving simulation. The collected data were analyzed and categorized based on complaint levels. The results showed that the most frequent complaints occurred in the lower back (score 12), followed by the lower neck, buttocks, and hips (score 11). The average overall score was 71.67, indicating a high-risk category. The highest individual score was 89 (Driver 3), and the lowest was 62 (Driver 1). These complaints were caused by the absence of an ergonomic driver seat in the prototype car. The study concluded that the current cockpit design is not ergonomically adequate, posing a risk of injury. Therefore, it is recommended that the design team immediately create a more upright driver seat with thigh support to enhance comfort and reduce musculoskeletal complaints.